Millimetric spatial resolution time-expanded ϕ-OTDR - Miguel Soriano-Amat; Philippe Guay; Hugo F. Martins; Sonia Martin-Lopez; Miguel Gonzalez-Herraez; María R. Fernández-Ruiz; Jerome Genest (APL Photonics, 2023)
Time-expanded phase-sensitive optical time-domain reflectometry is a distributed optical fiber sensing technology based on dual-frequency combs that allows for dynamic and high spatial resolution measurements while maintaining reduced detection requirements. Since the formalization of the technique, different experimental schemes have been satisfactorily tested, with a general performance of cm-scale spatial resolution over hundreds of meters. In this article, we present an optimized scheme with enhanced energy and spectral efficiencies that allows reaching 5 mm spatial resolution. As compared to previous experimental approaches, the presented architecture is based on a free-running dual comb setup generated through pure electro-optical phase modulation. Besides, the introduction of an optical hybrid in the detection stage allows for doubling the spatial resolution while keeping the refresh rate and the sensing range unchanged.